Disease detection of brucellosis in goat population in Negeri Sembilan, Malaysia - Mohd Yusof, Siti Sumaiyah; Haron, Abd Wahid; Bejo, Siti Khairani (2012)
A serological study of brucellosis in goats caused by Brucella melitensis was conducted in the state of Negeri Sembilan, Malaysia. A total of 771 serum samples were collected from seven districts namely Rembau, Jelebu, Kuala Pilah, Seremban, Port Dickson, Jempol, and Tampin. At least two farms were selected and a minimum of 100 serum samples were collected from each district. All sera were tested for brucellosis using the Rose Bengal plate test (RBPT) and complement fixation test (CFT). In this study, only Rembau and Kuala Pilah showed seropositivity for B. melitensis with RBPT and CFT at 1.0 and 2.5%, respectively. The CFT was more sensitive than the RBPT because the serum antibodies against B. melitensis detected by CFT were twice higher than that detected by RBPT. As suggested by the Office International des Epizooties OIE, CFT was used as a confirmatory test for brucellosis. This test is also recommended as a prescribed test for international trade and is used in the control and eradication programmes.